Characterizing ecotoxicity impacts of pesticides applied to vegetable crops in Finland during 2003–2019 and recommendations for impact reduction - Räsänen, Kati; Vänninen, Irene; Kurppa, Sirpa; Kukkonen, Jussi V.K.; Fantke, Peter (Elsevier, 2025)
Information on crop-specific pesticide use and environmental impact over time is currently limited. We used longitudinal data, covering 57 pesticides applied to carrot, potato, swede and fresh pea on more than 100 farms in southwestern Finland in 2003–2019. We combined these data with results from mass balance models to estimate emission fractions and characterization factors combining fate, exposure and effects to derive potential freshwater ecotoxicity impacts. Impacts varied across crops and pesticides and are dominated by a few substances. Spray frequencies and quantities across pesticides varied over the period considered, differing up to five orders of magnitude across crops. Combined with ecotoxicity potentials, this leads to differences in ecotoxicity impacts per hectare-year of more than seven orders of magnitude, ranging from 0.0005 PAF m3 d (Potentially Affected Fraction of species, PAF, integrated over exposure volume and time) for carrot to 16,000 PAF m3 d for potato. The three most ecotoxic pesticides in our study (lambda-cyhalothrin, cypermethrin, alpha-cypermethrin) rank among the top 1 % in USEtox, while other pesticides are at least a factor of 10 less ecotoxic, with potencies ranging over six orders of magnitude. Following our approach, pesticides can be ranked in terms of their environmental impact and the most hazardous pesticides identified for possible replacement with less harmful alternatives. This can inform pesticide substitution and other impact reduction measures in Finland, highlights that pesticide use alone is insufficient to indicate impacts, and has the potential to be applied to other pesticides, crops and regions.
Keywords: crop production; plant protection products; freshwater ecotoxicity impact assessment; USEtox; chemical substitution